2021
DOI: 10.4103/tjo.tjo_30_21
|View full text |Cite
|
Sign up to set email alerts
|

Vitreoretinal abnormalities in corona virus disease 2019 patients

Abstract: The coronavirus disease 2019 (COVID-19) has become a global pandemic since December 2019. Although COVID-19 primarily affects the respiratory systems, it has become abundantly clear that it involves multiple organs including the heart, kidney, skin, and brain. Neuro-ophthalmic signs and anterior segment inflammation of the eyes were documented in COVID-19 patients recently. Small but growing number of literatures has also reported the cases of new onset vitreoretinal disorders related to COVID-19 infection. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…The retina can be involved during or after COVID-19 ( 27 ), the mechanism of which is supposed to be related to the direct viral ocular infection because of the expression of ACE2 receptors in the retina, as well as the indirect effect of COVID-19 on vascular inflammation and thromboembolic complications ( 28 ). Some patients reported positive PCR retinal tests, while others did not ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The retina can be involved during or after COVID-19 ( 27 ), the mechanism of which is supposed to be related to the direct viral ocular infection because of the expression of ACE2 receptors in the retina, as well as the indirect effect of COVID-19 on vascular inflammation and thromboembolic complications ( 28 ). Some patients reported positive PCR retinal tests, while others did not ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Central retinal vein occlusion (CRVO) : According to the review studies, microvascular changes are the most common vitreoretinal disorder caused by COVID-19 infection ( 28 , 31 ). Impaired visual acuity was reported as a common complaint, while some were asymptomatic; various findings have also been reported to be found during the fundoscopic examination, such as retinal hemorrhages, and pan-retinal fern-like whitening ( 37 ), macular edema ( 38 ), dilated and tortuous vessels ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…The prothrombotic process begins with vasoconstriction, platelet activation, and increased proinflammatory cytokines [20] . Central retinal artery and vein occlusion, serpiginous choroiditis, macular hemorrhage, acute macular neuroretinopathy, paracentral acute middle maculopathy, vitritis, and acute retinal necrosis have been reported to develop in COVID-19 patients, as a result of direct viral invasion of the ocular vessel wall and the thromboembolic process [21] . Invernizzi et al have reported COVID-19 to affect retinal vascular structures and cause retinal hemorrhages, cotton wool spots, and dilated and tortuous vessels [22] .…”
Section: Discussionmentioning
confidence: 99%
“…This includes keratouveitis related to herpes zoster reactivation but affects many other cranial nerves as carefully reviewed and referenced in 54 . There is some evidence for vitritis that can be associated with uveitis 55 . Vitritis can also be present with some of the macular pathology discussed above.…”
Section: Autoimmunementioning
confidence: 99%